Triclosan inhibits testosterone synthesis in male offspring by activating mitophagy - Huili Lan; Yan Jiang; Lixiang Wu; Shushu Xie; Hui Huang; Dapeng Ji; Bingqi Zhu; Zhishan Ding; Jie Yu; Xiaoqing Ye (Ecotoxicology and Environmental Safety)
Triclosan (TCS), a typical endocrine disruptor, has been shown to interfere with testosterone biosynthesis in male animals. However, the effects and mechanisms of environmental TCS levels on testosterone synthesis in male mice offspring remain unclear. In this study, male mice offspring were exposed to TCS (0, 30, 300, and 3000 μg/kg/day) during prenatal and lactation periods, and Leydig (TM3) cells exposed to TCS (0, 30, 300 and 3000 nM) were used to establish an in vitro model. Results indicated that TCS exposure led to reduced testicular weight, organ coefficient, serum testosterone levels and steroidogenic enzyme activity, along with pathological changes in testicular tissue. RNA sequencing and lipid metabolome analysis suggested that TCS exposure may disrupt testicular lipid metabolism and is closely related to mitophagy and the PI3K/AKT/mTOR pathway. For in vitro experiments, TCS activated mitophagy in TM3 cells, characterized by elevated reactive oxygen species, mitochondrial damage, reduced mitochondrial membrane potential, formation of mitochondrial phagosomes and phagolysosomes, and altered expression of mitophagy-related proteins. TCS also decreased PI3K/AKT/mTOR pathway activity and steroidogenic enzyme expression, inhibiting testosterone secretion. In conclusion, environmental TCS levels inhibit testosterone synthesis in male offspring by inducing Leydig cell mitophagy, which may be linked to the suppression of the PI3K/AKT/mTOR pathway.